Hubungan Pengetahuan Tentang Manajemen Laktasi Pada Ibu Bekerja Dengan Pemberian ASI Ekslusif - Putri, Poppy Siska; Syafitasari, Juanda (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
The lack of exclusive breastfeeding is generally due to insufficient milk production, leading to the cessation of exclusive breastfeeding practices. The main factor in the failure of exclusive breastfeeding is lactation mismanagement during the breastfeeding period. Adequate knowledge can increase working mothers' self-efficacy and help working mothers continue to breastfeed during the transition back to the workforce. This study aimed to see the relationship between knowledge about lactation management in working mothers with exclusive breastfeeding in the Working Area of Sidomulyo Health Center, Bengkulu City. The sample size was 58 respondents, who were given questionnaires using the Gutman scale. The results of statistical tests using chi-square with a p-value of 0.019 < < 0.05 and an Odds Ratio of 3,800 show there is a significant relationship between knowledge of lactation management in working mothers with exclusive breastfeeding. Working mothers are expected to increase their knowledge by attending breastfeeding classes or utilizing social media about lactation management to provide breast milk still while working.